Program Wirausaha Muda Bank Mandiri sebagai Implementasi Corporate Social Responsibility Sesuai PP No. 47/2012 - Akhyar, Dani Miftahul (REFORMASI, 2024)
Changes in the business competition landscape have forced companies to realize the importance of managing and improving a positive reputation in the eyes of stakeholders, one of which is done by creating a corporate social responsibility (CSR) program. This research discusses the implementation of CSR which is carried out in improving the company's reputation through its implementation in the "Mandiri Young Entrepreneur (WMM)" program. This CSR program from Bank Mandiri has been implemented since 2007 until now. However, this research limits the program implementation period to the first five years of its implementation, namely 2007-2012. The type of research used is qualitative with the nature of descriptive research and case studies. Data collection methods were carried out through in-depth interviews and literature study. The research results show that the WMM program has also run well from the CSR planning strategy stage to implementation. The company's reputation in the eyes of program participants and the community increases as seen from the output and outcomes obtained from implementing this WMM program. Among other things, it can be seen from the level of company publicity which has continued to increase since 2007-2012, and the many awards received by this WMM program from various institutions.AbstrakPerubahan lanskap persaingan bisnis telah memaksa perusahaan utnuk menyadari pentingnya mengelola dan meningkatkan reputasi yang positif di mata stakeholders, yang salah satunya dilakukan dengan membuat program corporate social responsibility (CSR). Penelitian ini membahas tentang implementasi (CSR) yang dijalankan dalam meningkatkan reputasi perusahaan melalui implementasinya pada program “Wirausaha Muda Mandiri (WMM)”. Program CSR dari Bank Mandiri ini telah dijalankan sejak tahun 2007 hingga sekarang. Namun penelitian ini membatasi periode pelaksanaan program di lima tahun pertama pelaksanannya yaitu tahun 2007-2012. Jenis penelitian yang digunakan adalah kualitatif dengan sifat penelitian deskriptif dan studi kasus. Metode pengumpulan data dilakukan melalui wawancara mendalam dan studi kepustakaan. Hasil penelitian menunjukkan bahwa program WMM juga telah berjalan dengan baik mulai dari tahapan strategi perencanaan CSR hingga implementasi. Reputasi perusahaan di mata peserta program dan masyarakat meningkat dilihat dari output dan outcome yang didapatkan dari pelaksanaan program WMM ini. Antara lain dilihat dari level publisitas perusahaan yang terus meningkat sejak tahun 2007-2012, dan banyaknya penghargaan yang diterima oleh program WMM ini dari berbagai lembaga.